Obstacles on the Road to School: The Impacts of Mobility Restrictions on Educational Performance - Sami H. Miaari; Ines Lee (Institute of Labor Economics (IZA), 2020)
This paper examines the impact of mobility restrictions on educational performance in the West Bank over 2000–2006 during the Israeli-Palestinian conflict. This conflict is characterized by a system of mobility restrictions enforced through physical barriers such as checkpoints. Using novel data on the location of barriers, we find that exposure to one or more checkpoints reduces the probability of passing the final high school exam by 1–3 percentage points and the overall score by 0.04–0.07 standard deviations. We find evidence of three mechanisms at play: school resources deteriorate, students' psychological wellbeing worsens, and students lose time due to delays at checkpoints.
Keywords: D74; I25; J61; 330; education; academic achievement; test score; conflict; fatalities; mobility; closures